Livestock Environment VIII, 31 August - 4 September 2008, Iguassu Falls, Brazil 2008
DOI: 10.13031/2013.25593
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Black Globe Temperature Based on Meteorological Data

Abstract: An automatic weather station, comprising of temperature and humidity sensors, a pyranometer, an anemometer, and a thermocouple inside a black globe, was installed in a grassed area at the University of the State of Bahia-UNEB, Juazeiro County, Bahia State, Brazil. Half of the data collected at this station was used to generate models (simple or multiplicative) for estimating the Black Globe Temperature (BGT). Model performance was evaluated by using the second half of the data. Statistical precision and accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The required input T mrt may be derived, assuming that it is a linear function of t a [51,52], i.e., radiant flux densities are only estimated. In more recent approaches, T mrt is explicitly derived from readily available standard meteorological data that include the above-mentioned data from active radiometry (e.g., [24,34,53,54,67]). Here, T mrt,r,BG can be calculated for a black globe by means of Equation (3) using f p = 0.25 and α sw,Sk = 0.95.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The required input T mrt may be derived, assuming that it is a linear function of t a [51,52], i.e., radiant flux densities are only estimated. In more recent approaches, T mrt is explicitly derived from readily available standard meteorological data that include the above-mentioned data from active radiometry (e.g., [24,34,53,54,67]). Here, T mrt,r,BG can be calculated for a black globe by means of Equation (3) using f p = 0.25 and α sw,Sk = 0.95.…”
Section: Discussionmentioning
confidence: 99%
“…Then, Equation ( 7) is solved for T g by iteration or by using empirical/polynomial methods. As this study found, it is advantageous for such empirical approaches to differentiate during the daytime between conditions in which the black globe is sunlit or is shaded [50] and to address separately nighttime data that are more closely linked to t a (Figure 4a) [54,69]. From the correlation of modeled against observed t g [49,50,54] and from the difference T mrt,Tg,BG − T mrt,r,KMM as a function of t g [70], it is apparent that the observed t g exhibits the same problem as seen here, especially under sunny conditions (see Figure 4a,b, Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation